The effect of Portulaca oleracea (purslane) seeds on hemoglobin levels in adolescent girls with iron deficiency anemia: a randomized comparative trial - Mokhtarifar, Ali; Zeydabadi, Fatemeh Asadi; Asili, Javad; Kooshyar, Mohammad Mahdi; Sahebkar, Amirhossein (Comparative clinical pathology, 2017)
Iron deficiency anemia (IDA) is the most severe and the latest stage of iron deficiency. Consumption of purslane seeds is a traditional medicine approach for the treatment of anemia. We aimed to compare the effect of purslane seeds and ferrous sulfate (FS) on the hemoglobin (Hb) level of adolescent girls suffering from IDA. In this single-blind randomized comparative clinical trial, the effect of purslane seeds was compared with a FS tablet in 53 adolescent girls. Included subjects were within the age range of 15–18 years; with Hb levels of 10–12 g/dL and serum ferritin levels lower than 12 ng/L. The experimental group received 0.3 g/kg of purslane seeds and control group received 3 mg/kg of elemental iron as a standard control per day for a period of 4 weeks. There were significant increases in hemoglobin (Hb), hematocrit (Hct), and mean corpuscular volume in both purslane and FS groups; however, the mean elevation was significantly greater with the latter. FS also caused a significantly greater increase in red cell distribution width compared with purslane. Purslane seed consumption increases Hb and Hct levels but is less effective than FS. Purslane seeds may be used for the prevention of IDA and treatment of its mild form.